Bridging The Gap: Parental Involvement in Digital Classrooms in Elementary Schools - Vega Hesmatantya; Armeria Wijaya (Prosiding Konferensi Ilmiah Dasar, 2024)
This case study explores the involvement of parents in accompanying their children in online learning activities at the elementary school level. The parents' demographics as participants in this research are very diverse. Due to the Covid-19 outbreak, elementary school learning has transformed from face-to-face to online. This has become a significant concern for parents because online learning is new. Participated by two hundred respondents and followed by twelve respondents in the interview stage, this research attempts to examine how parents perceive their roles and responsibilities in supporting their children’s online learning activities at the elementary school level, then investigate the main challenges faced by parents in supporting their children's transition from face-to-face to online learning during the Covid-19 outbreak. The result shows that parents put hardly any effort into fulfilling their roles as learning companions for their children. This situation can still be managed well for parents whose fathers work and the mother is a housewife because the mother has much time. However, this situation is very difficult for working mothers as they have to juggle their time to provide sufficient support. Thus, it can be concluded that if online learning continues to be implemented in a hybrid format at the elementary school level, it is imperative to establish clear and intensive communication among teachers, students, and parents regarding the learning modes employed to ensure greater effectiveness and efficiency. Furthermore, it is essential to implement systems for regular monitoring and feedback to assess the effectiveness of parental involvement and identify the challenges they encounter.